TRophicPosition, an r package for the Bayesian estimation of trophic position from consumer stable isotope ratios. Issue 6 (23rd April 2018) - Quezada‐Romegialli, Claudio; Jackson, Andrew L.; Hayden, Brian; Kahilainen, Kimmo K.; Lopes, Christelle; Harrod, Chris
Abstract: Stable isotope analysis provides a powerful tool to identify the energy sources which fuel consumers, to understand trophic interactions and to infer consumer trophic position (TP), an important concept that describes the ecological role of consumers in food webs. However, current methods for estimating TP using stable isotopes are limited and do not fulfil the complete potential of the isotopic approach. For instance, researchers typically use point estimates for key parameters including trophic discrimination factors and isotopic baselines, and do not explicitly include variance associated with these parameters when calculating TP. We present "tRophicPosition, " an r package incorporating a Bayesian model for the calculation of consumer TP at the population level using stable isotopes, with one or two baselines. It combines Markov Chain Monte Carlo simulations through JAGS and statistical and graphical analyses using R. We model consumer and baseline observations using relevant statistical distributions, allowing them to be treated as random variables. The calculation of TP—a random parameter—for one baseline follows standard equations linking 15 N enrichment per trophic level and the trophic position of the baseline (e.g. a primary producer or primary consumer). In the case of two baselines, a simple mixing model incorporating δ 13 C allows for the differentiation between two distinct sources of nitrogen, thus including heterogeneity derived from alternatives sources of δ 15 N. Methods currently implemented in "tRophicPosition " include loading, plotting and summarizing stable isotope data either from multiple sites and/or communities or a local assemblage; loading trophic discrimination factors from an internal database or generating them; defining and initializing a Bayesian model of TP; sampling posterior parameters; analysing, comparing and plotting posterior estimates of TP and other parameters; and calculating a parametric (non‐Bayesian) TP estimate. Additionally, full documentation including examples, multiple vignettes and code are available for download. Foreign Language Abstract Resumen: El análisis de isótopos estables es una poderosa herramienta para identificar qué vías energéticas alimentan a los consumidores, para entender las interacciones tróficas, y también para inferir la posición trófica (PT) de los consumidores, un concepto importante que describe el rol ecológico de los consumidores en las tramas tróficas. Sin embargo, los métodos actuales para estimar la PT utilizando isótopos estables están limitados y no permiten alcanzar el potencial de la aproximación isotópica. Por ejemplo, los investigadores típicamente utilizan estimaciones puntuales de parámetros claves incluyendo factores de discriminación trófica y líneas base isotópicas, y no incorporan explícitamente la varianza asociada con estos parámetros cuando calculan la PT. Presentamos "tRophicPosition, " un paquete de R para isótopos estables que incorpora un modelo Bayesiano para el cálculo de la PT en consumidores al nivel ecológico de población, con una o dos líneas base. Este paquete combina simulaciones de cadenas de Markov Monte Carlo a través de JAGS y utilizando los análisis estadísticos y gráficos de R. Modelamos las observaciones de consumidores y líneas base utilizando distribuciones estadísticas relevantes, por lo que son tratadas como variables aleatorias. El cálculo de la PT—un parámetro aleatorio—para una línea base considera ecuaciones estándar que vinculan el enriquecimiento en 15 N por nivel trófico y el nivel trófico de la línea base (p.e. un productor primario o un consumidor primario). En el caso de dos líneas base, un modelo de mezcla simple incorporando δ 13 C permite la diferenciación entre dos fuentes distintas de nitrógeno, incluyendo de esta forma la heterogeneidad derivada de fuentes alternativas de δ 15 N. Los métodos actualmente implementados en "tRophicPosition " incluyen cargar, graficar y resumir datos de isótopos estables desde múltiples sitios y/o comunidades o ensambles locales; cargar factores de discriminación trófica desde una base de datos interna o generarlos; definir e inicializar un modelo Bayesiano para la PT; muestrear parámetros a posteriori ; analizar, comparar y graficar estimaciones a posteriori de la TP y otros parámetros; y calcular una estimación frecuentista (no Bayesiana) para la PT. Adicionalmente, toda la documentación incluyendo ejemplos, distintas viñetas y el código están disponibles para descarga.